PERANCANGAN FRAMEWORK VERIFIKASI QUALITY ASSURANCE PROSES MANUFAKTUR MENGGUNAKAN KEMAMPUAN DETEKSI DAN TINDAKAN KONDISI IRREGULAR - Abid, Muhammad Miftahul; Kusuma, Harun Indra; Ulfia, Yessi Nasia (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
Production process part body type car Rail Roof Side experience defect that is, there are variations in size specifications due to unstable processes. The cause of the unstable process is that the repair of the die tooling is not optimal and the machine parameters stamping not yet ideal for process operations. Verification quality assurace processes are needed to ensure QA is able to prevent, detect and control every production process activity. This research aims to design framework verification quality assurance by using detection capability variables and action conditions irregular. The process stability measurement variable using Cpk data is used as the main data. Design results framework process QA verification is a Cpk measurement >1.33 for a stable process standard, then a detection capability level during work operations of 0.8 for visual detection scores and tool detection capabilities, warnings, interlock system respectively 1.0/1.2/1.4. Meanwhile, the ability to detect post-work operations visually, tools, warnings, interlock system respectively 1.1/1.2/1.3/1.4. Meanwhile, the level of action ability irregular namely a score of 1 if the worker is able to take action according to the SOP and a score of 0 if the action does not comply with the SOP when there is an abnormal process. The final stage combines these 3 (three) variables to produce a rank value at each inspection point. Process quality assurance can be achieved if the rank value is 1.5–1.99 and the rank value is > 2.0. Process quality assurance is not achieved if the rank value is 0.0–1.19 and the rank value is 1.2–1.49. Process guarantees that are not achieved indicate that there are process variations or unstable processes. The verification process is considered complete when the results of the verification of process guarantees reach the target and improvements are made to quality guarantees that do not reach the target rank.